REAKTUALISASI FIKIH ZAKAT MENUJU ADMINISTRASI IDEAL - H. Jamaluddin (AL-IQTISHAD, 2020)
Abstract Religious obligatory obliged by Syara’ to having tired estae of nisab represent help to clan of du’afa. Religious obligatory can push them to work hotly and can push them to reach for competent life. With this action, society will is covert from disease of poorness, and state will be looked after from weakness and maltreatment. Less expanding religious obligatory institution it because to the number of problematika at religious obligatory institution, among others: rich criterium (muzakki), conversion religious obligatory, and ashnaf. Beside third problematika, also do not fail having an effect on it is Administration and religious obligatory management, speally credibility and accuntabilitas. Of that problematicaborn doubt, Being of muzakki to organizer, so that many more options muzakki deliver direct or look for institution which they trust. Kata Kunci: Reaktualisasi; fikih; zakat; administrasi.